Silver Bullet - Software Project Management Process Support Tool - Neves, Raul Nogueira; Dias, Matheus Boeira; Muller, Dionas; Araujo, Thiago C. de M.; Seibel, Inaiara S. dos S.; Bernardino, Maicon; Rodrigues, Elder de Macedo; Basso, Fabio Paulo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2025.11605, 2025)
Software engineering is essential to modern software development, encompassing methodologies, tools, and practices to ensure quality, maintainability, and adherence to deadlines and budgets. However, many software projects still fail due to poor or absent management practices. According to the Project Management Institute (PMI), organizations with a strong project management culture achieve a 71% success rate and significantly fewer financial losses. In response to the need for better training in software management, the Silver Bullet tool. was created in 2018 to support teaching and learning aligned with PMI’s PMBOK®. Initially developed for the Problem Solving VI course in a Software Engineering program, the tool aimed to improve both project outcomes and management practices. Since then, it has evolved beyond academia, contributing to professional training and addressing challenges in software project success. The ongoing development of Silver Bullet reflects advancements in educational tools and the broader effort to strengthen the software engineering field. License: Subscription License (SaaS). Demo video: https://doi.org/10.5281/zenodo.16237208 .